Nickel-doped cerium oxide nanoparticles: Green synthesis using stevia and protective effect against harmful ultraviolet rays - Khatami, Mehrdad; Sarani, Mina; Mosazadeh, Faride; Rajabalipour, Mohammadreza; Izadi, Alireza; Abdollahpour-Alitappeh, Meghdad; Nobre, Marcos Augusto Lima [UNESP]; Borhani, Fariba (MDPI, 2019)
Nanoparticles of cerium oxideCeO2 are important nanomaterials with remarkable properties for use in both industrial and non-industrial fields. In a general way, doping of oxide nanometric with transition metals improves the properties of nanoparticles. In this study, nickel- doped cerium oxide nanoparticles were synthesized from Stevia rebaudiana extract. Both doped and non-doped nanoparticles were characterized by X-ray diffraction, Field Emission Scanning Electron Microscopy, Energy Dispersive X-ray, Raman spectroscopy, and Vibrating-Sample Magnetometry analysis. According to X-ray diffraction, Raman and Energy Dispersive X-ray crystalline and single phase of CeO2 and Ni doped CeO2 nanoparticles exhibiting fluorite structure with F2g mode were synthesized. Field Emission Scanning Electron Microscopy shows that CeO2 and Ni doped nanoparticles have spherical shape and sizes ranging of 8 to 10 nm. Ni doping of CeO2 results in an increasing of magnetic properties. The enhancement of ultraviolet protector character via Ni doping of CeO2 is also discussed.
Keywords: Ni-doped CeO2 nanoparticles; Stevia rebaudiana; UV protection; VSM